Republic of Kazakhstan : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper and Statistical Appendix describes economic developments in the Republic of Kazakhstan during 1996-99. The paper provides information on the magnitude of large external shocks felt by Kazakhstan during 1998, describes the policy approach taken by the Kazakh authorities in response to these shocks, and summarizes developments in the real, monetary, fiscal, and external sectors in 1998 and the first quarter of 1999. The paper also contains a brief account of progress on structural reforms.